1864 Idaho Sess. Laws 442 - (:unkn) unknown (My University, 1864)
An Act Concerning Crimes and Punishments, § 40: Prohibited brandishing any dirk, dirk-knife, sword, sword-cane, pistol, gun, or other deadly weapon in the presence of two or more persons in a rude, angry, or threatening manner. Violators fined not less than one hundred nor more than five hundred dollars.
Keywords: BRANDISHING